Poetyka filmów szkoły polskiej (kilka refleksji o inspiracjach) - Alicja Helman (Postscriptum Polonistyczne)
The article is devoted to the Polish Film School. The origins of the phenomenon are presented against the background of Polish cinema in postcommunist times. The author emphasizes the impact of Italian neorealism upon the Polish Film School, which is strongly reflected in cinematography. Also similarities with and inspirations from German expressionism are traced. Critics’ opinions on the most significant films from the Polish Film School and the movement itself are cited.